Tabetri™ (Tabebuia avellanedae Ethanol Extract) Ameliorates Osteoarthritis Symptoms Induced by Monoiodoacetate through Its Anti-Inflammatory and Chondroprotective Activities - Park, Jae Gwang; Yi, Young-Su; Hong, Yo Han; Yoo, Sulgi; Han, Sang Yun; Kim, Eunji; Jeong, Seong-Gu; Aravinthan, Adithan; Baik, Kwang Soo; Choi, Su Young; Son, Young-Jin; Kim, Jong-Hoon; et al. (Mediators of Inflammation, 2017)
Although osteoarthritis (OA), a degenerative joint disease characterized by the degradation of joint articular cartilage and subchondral bones, is generally regarded as a degenerative rather than inflammatory disease, recent studies have indicated the involvement of inflammation in OA pathogenesis. Tabebuia avellanedae has long been used to treat various diseases; however, its role in inflammatory response and the underlying molecular mechanisms remain poorly understood. In this study, the pharmacological effects of Tabetri (Tabebuia avellanedae ethanol extract (Ta-EE)) on OA pathogenesis induced by monoiodoacetate (MIA) and the underlying mechanisms were investigated using experiments with a rat model and in vitro cellular models. In the animal model, Ta-EE significantly ameliorated OA symptoms and reduced the serum levels of inflammatory mediators and proinflammatory cytokines without any toxicity. The anti-inflammatory activity of Ta-EE was further confirmed in a macrophage-like cell line (RAW264.7). Ta-EE dramatically suppressed the production and mRNA expressions of inflammatory mediators and proinflammatory cytokines in lipopolysaccharide-stimulated RAW264.7 cells without any cytotoxicity. Finally, the chondroprotective effect of Ta-EE was examined in a chondrosarcoma cell line (SW1353). Ta-EE markedly suppressed the mRNA expression of matrix metalloproteinase genes. The anti-inflammatory and chondroprotective activities of Ta-EE were attributed to the targeting of the nuclear factor-kappa B (NF-κB) and activator protein-1 (AP-1) signaling pathways in macrophages and chondrocytes.